1998
DOI: 10.1046/j.1365-2265.1998.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of insulin, insulin‐like growth factor(IGF)‐I, IGF binding protein (IGFBP)‐1 and ‐3 and growth hormone binding protein in obese children: fasting IGFBP‐1 is suppressed in normoinsulinaemic obese children

Abstract: The present study showed for the first time that the fasting IGFBP-1 level was suppressed in prepubertal obese children with fasting normoinsulinaemia. We speculate that the hyperinsulinaemia which cannot be detected in the fasting state may have suppressed hepatic production of IGFBP-1. Alternatively, the reduced IGFBP-1 is likely to be a compensatory response to impaired insulin sensitivity. Thus, the IGFBP-1 level may be a useful predictor for the early identification in the development of insulin resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 43 publications
4
30
2
Order By: Relevance
“…A recent study has suggested that suppression of the insulin-like growth factor-binding protein-1 (IGFBP-1) level due to hyperinsulinemia increases the level of free insulin-like growth factor-I (IGF-I) and promotes IGF-I's action, resulting in normal growth despite the reduced GH secretion in obese children (7). We have also reported that the serum IGFBP-1 level is suppressed in prepubertal obese children with fasting normoinsulinemia (8).…”
Section: Introductionmentioning
confidence: 62%
“…A recent study has suggested that suppression of the insulin-like growth factor-binding protein-1 (IGFBP-1) level due to hyperinsulinemia increases the level of free insulin-like growth factor-I (IGF-I) and promotes IGF-I's action, resulting in normal growth despite the reduced GH secretion in obese children (7). We have also reported that the serum IGFBP-1 level is suppressed in prepubertal obese children with fasting normoinsulinemia (8).…”
Section: Introductionmentioning
confidence: 62%
“…Circulating IGF-I levels in obese subjects would be expected to be low, because growth hormone (GH) stimulates the liver to produce IGF-I and because there is an inverse relationship between obesity and GH secretion. However, findings of studies on obese subjects are conflicting, with serum concentrations of total IGF-I reported to be relatively low, 13-16 unchanged 17,18 or increased. 19,20 Several crosssectional studies of adiposity and circulating IGF-I have found no relationship [21][22][23][24][25][26][27][28][29][30][31][32] while a nonlinear relationship of body mass index (BMI) with IGF-I has been observed in some large studies.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is associated with a state of GH resistance (Soliman et al, 1986). On the other hand, obesity leads to lower GH but high to normal IGF-I levels in children (Loche et al, 1987;Argente et al, 1997;Falorni et al, 1997;Saitoh et al, 1998). In developing countries, malnutrition is more common in children from lower socioeconomic levels and the obesity is more common in children from higher socioeconomic levels (Gross et al, 1990;Peck and Lundberg, 1995;Nebigil et al, 1997;Hakeem, 2001;Ulukanligil and Seyrek, 2004a).…”
Section: Introductionmentioning
confidence: 99%